Dissociated Retinal Cell Culture - Christine Jolicoeur; Michel Cayouette (Bio-Protocol, 2014)
The retina is a relatively simple and accessible part of the central nervous system, making it a powerful model to study cell fate specification mechanisms. Multipotent retinal progenitor cells (RPCs) give rise to seven major classes of retinal cell types. Mechanisms regulating cell fate choice in the retina depend on both cell intrinsic and environmental factors, but their relative contribution to specific cell fate decisions remains unclear. Dissociated retinal cell cultures provide a great assay to study this problem. RPCs are cultured in serum-free and extract-free medium, providing the investigator with a control over the environment to address questions related to the effects of a particular molecule on the development of retinal neurons. In addition, dissociated cell cultures can be used to study the importance of cell intrinsic mechanisms by isolating RPCs from their normal environment (Cayouette et al., 2003; Jensen and Raff, 1997). The method described below is suitable for the clonal-density culture of RPCs. In such cultures, RPCs are isolated from each other and from the postmitotic neurons. They divide and differentiate into different retinal cell types to form small colonies, or “clones”. In a recent study, we found that these clones are indistinguishable from the clones that develop in situ in the retina, both in terms of cell number and cell type composition, suggesting that intracellular mechanisms play a key role in retinal development (Cayouette et al., 2003).